The club by David Williamson : Sydney Theatre Company - Sydney Theatre Company ([Sydney : The Company], 2003)
Steve Bisley sits at left, Conrad Coleby centre, and John Wood at right.
Part of: Collection of Sydney Theatre Company posters.
Title devised by cataloguer.
Digital master available
Keywords: Williamson, David, -- 1942 February 24- . -- Dramatic production -- Posters; Sydney Theatre Company -- Posters; Theater -- New South Wales -- Sydney -- Posters; Theatrical posters -- New South Wales -- Sydney